Barley pathogens in Iceland: Identification, virulence and genetic structure of major barley pathogens in Iceland - Tryggvi Sturla Stefánsson 1982- (2009)
Leaf samples were collected from 27 barley fields in Iceland in August 2007 in order to analyze the diversity of fungal species growing on barley. Twelve fungal species were found on 277 successfully analyzed leaves, including two widespread barley pathogens, Rhynchosporium secalis and Pyrenophora teres f. teres, the causal agents of scald and net blotch, respectively. The genetic structure of the Icelandic R. secalis population was studied using thirteen microsatellite markers and results compared to six European R. secalis populations. The genetic structure of P. teres was examined with four AFLP markers and compared to populations from Finland and Russia. Both studies revealed a significant differentiation between the Icelandic and European populations. The mean Fst value between the Icelandic R. secalis population and five Scandinavian populations was 0.165 and pairwise differentiation between the P. teres populations from Iceland and Finland was 0.640. Of the P. teres populations analyzed the gene diversity was highest in Iceland, with a value of 0.26, compared to 0.17 and 0.04 in the Russian and Finnish populations, respectively. The gene diversity in the seven R. secalis populations ranged from 0.43-0.73 and was 0.55 in Iceland. The distribution of genetic diversity was notably different for the R. secalis and P. teres populations as 84% of the total diversity was distributed within populations and only 16% between populations for R. secalis where as more than half of the total genetic diversity, or 51%, was distributed between the P. teres populations and only 49% distributed within the three populations. The existence of mating types 1 and 2 at the same locations was confirmed in both R. secalis and P .teres populations from Iceland, providing evidence of sexual reproduction. The virulence of Icelandic R. secalis and P. teres populations was assessed on a number of standard barley genotypes. Both populations had high pathogenic variation. Fourteen R. secalis isolates were grouped into eleven pathotypes ...